Updates in Reproduction Coming from the Endocannabinoid System - Rosaria Meccariello; Natalia Battista; Heather B. Bradshaw; Haibin Wang (International Journal of Endocrinology)
The endocannabinoid system (ECS) is an evolutionarily conserved master system deeply involved in the central and local control of reproductive functions in both sexes. The tone of these lipid mediators—deeply modulated by the activity of biosynthetic and hydrolyzing machineries—regulates reproductive functions from gonadotropin discharge and steroid biosynthesis to the formation of high quality gametes and successful pregnancy. This review provides an overview on ECS and reproduction and focuses on the insights in the regulation of endocannabinoid production by steroids, in the regulation of male reproductive activity, and in placentation and parturition. Taken all together, evidences emerge that the activity of the ECS is crucial for procreation and may represent a target for the therapeutic exploitation of infertility.